MARKETING STRATEGY FOR DELTA KAYAN FOOD ESTATE DEVELOPMENT IN BULUNGAN DISTRICT, NORTH KALIMANTAN PROVINCE - Puteri Aprilani; Masyhuri Masyhuri; Suhatmini Hardyastuti (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2023)
Bulungan Regency, which is located in North Kalimantan, is one of the areas chosen by the government to be an area for the use of tidal swampland for rice cultivation because the area of swampland owned is quite as large as 50 hectares of the area named Delta Kayan Food Estate. However, in its implementation, farmers have obstacles to market the rice harvest they produce. This research was conducted to create a strategy for the development of tidal swamp rice produced by Delta Kayan Food Estate. The survey was conducted on 30 purposively selected respondents. The data were collected through interviews with structured questionnaires using the SWOT analysis method and looked at the priority strategies to be carried out using the QSPM analysis. From the results of the SWOT analysis.